2010
DOI: 10.1253/circj.cj-10-0540
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Aortic Root Using Real-Time 3D Transesophageal Echocardiography

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp ecause of the rapid increase in cases of calcific aortic stenosis (AS) in industrialized countries, there are increasing numbers of symptomatic elderly patients who do not undergo aortic valve surgery because the surgical intervention poses significant risks related to coexisting comorbidities. 1,2 As a result, there are growing concerns regarding the poor prognosis of these patients and the increased associated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 31 publications
7
68
0
1
Order By: Relevance
“…In addition, the procedure is simple. 15 The results of the present study indicate the simplicity of valved stent implantation above the coronary ostia. The stent designed for the experiment was braided with super elastic nickel-titanium alloy wires, which allowed the stent to comply better and to attach to the aortic wall easily.…”
Section: Feasibility Of Percutaneous Aortic Valved Stent Implantationsupporting
confidence: 58%
“…In addition, the procedure is simple. 15 The results of the present study indicate the simplicity of valved stent implantation above the coronary ostia. The stent designed for the experiment was braided with super elastic nickel-titanium alloy wires, which allowed the stent to comply better and to attach to the aortic wall easily.…”
Section: Feasibility Of Percutaneous Aortic Valved Stent Implantationsupporting
confidence: 58%
“…Otani et al [5] have reported a very good correlation between these two methods to assess the planimetric area of the outflow tract (r=0, 96 mean diference: 0.35 ± 0.29 cm ). This method would also allow modifying the continuity formula regularly used in the estimation of the aortic valve area (AVA).…”
Section: Discussionmentioning
confidence: 93%
“…We can add that not always the bi dimensional cut passes through the central LVOT axis which is another source of potential error [2]. At present, different studies have confirmed that LVOT anatomy is more elliptic than circular; a significant decrease of the estimated LVOT area related to the area measured by planimetry [3][4][5][6] is also observable. This contributes to underestimate both larger and smaller LVOT diameters, which are essential for the correct choice of percutaneous prosthesis, increasing the risk of perivalvular leaks, and prosthesis migration, among other complications [7].…”
Section: Discussionmentioning
confidence: 94%
“…However, information obtained from both three-dimensional transesophageal echocardiography and multidetector computed tomography has shown that LVOT shape is not round but elliptical. 36,37) Thus, the 2D longaxis view does not always depict the longest span of LVOT, resulting in an underestimation of its full diameter. Limitations: The present study had several limitations.…”
Section: Discussionmentioning
confidence: 99%